A survey of molecular clouds in the outer Galaxy with the highest spatial resolution. Issue Volume 11:Issue S321(2015) (21st March 2017) - Matsuo, Mitsuhiro; Minamidani, Tetsuhiro; Umemoto, Tomofumi; Nishimura, Atsushi; Nakanishi, Hiroyuki; Kuno, Nario; Fujita, Shinji; Tosaki, Tomoka; Tsuda, Yuya; Yamagishi, Mitsuyoshi; Kohno, Mikito; ,
Abstract: We report a recent result of the FUGIN project, a Galactic plane CO survey using the Nobeyama 45-m Telescope and the FOREST receiver. In the third galactic quadrant, 42 square degrees are observed and 4752 molecular clouds are detected. Among them, 12 clouds are located at R (distance from the Galactic center) > 16 kpc. Molecular clouds at R < 16 kpc trace the Local, Perseus, and Outer arms.